2021
DOI: 10.11594/10.11594/ijmaber.02.11.12
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Case Study on the Challenges Encountered by Philippine Private and Public Educational Institutions with their Existing Management Information System

Abstract: For the last two years, all Philippine educational institutions had to adapt flexible learning. All personnel and students underwent orientation and training to their institution’s Management Information System (MIS). These institutions are utilizing either MIS mandated by the Department of Education, subscribed to or created by the institution itself. Challenges and concerns have been noted on the use of these MIS worldwide. Hence, this study elucidated the experiences and challenges of admistrators, faculty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…However, the finance MIS found that it needs further enrichment in planning, implementation, and evaluation. Another study from Zulueta et al (2021) also discussed the challenges encountered by Philippine private and public educational institutions with an existing management information system. They divulged that these participating schools have an excellent way to systematize and organize a work in progress encompassing all institutional services.…”
Section: Introductionmentioning
confidence: 99%
“…However, the finance MIS found that it needs further enrichment in planning, implementation, and evaluation. Another study from Zulueta et al (2021) also discussed the challenges encountered by Philippine private and public educational institutions with an existing management information system. They divulged that these participating schools have an excellent way to systematize and organize a work in progress encompassing all institutional services.…”
Section: Introductionmentioning
confidence: 99%